Use of social media and academic performance of students evidence from undergraduate students in university of jaffna, sri lanka - Jeyan Suganya, D.F.; Kengatharan, L.; Yogendrarajah, R. (University of Jaffna, 2020)
This study attempts to examine the impact of use of social media on academic performance of students. Primary data was collected from sample of hundred and eighty students who were following degree of Bachelor of Business Administration programme in faculty of management studies and commerce, University of Jaffna from first year to final year. Use of social media is measured using different dimensions such as time duration, addictiveness, exposure and nature of usage, while overall Grade Point Average is used to measure academic performance of the students issuing structured questionnaires. Descriptive statistics, correlation analysis, multiple regression analysis and ANOVA test were employed to analyse collected data for the study. Result revealed that time duration in use of social media and addictiveness to social media have significant negative impact on academic performance of students, however, exposure to social media and nature of usage don’t have any significant impact on academic performance of students. Further, it was found that there is no significant difference in using hours of social media for educational and non-educational purpose among the students studying in different years. Finding of the study may lead the students to manage their valuable time spending in social media without negatively impact on their academic performance. The students may be encouraged to enhance their academic performance by using social media much more for educational purpose.
Keywords: Academic performance; Addictiveness; Exposure; Social media; Time duration